Lived experiences of Overseas Filipino Worker (OFW) nurses working in COVID-19 intensive care units - Jane Marnel Pogoy; Jezyl Cempron Cutamora (Belitung Raya Foundation, Indonesia, 2021)
Background: Limited studies focus on the effects of the pandemic on the nurses' overall risks and wellbeing. At present, no single study has been published on Filipino nurses’ experiences outside the country during the COVID-19 pandemic.Objective: This descriptive phenomenological study explored the Overseas Filipino Worker (OFW) nurses’ experiences working in COVID-19 intensive care units.Methods: The study was conducted in Dubai, United Arab Emirates, where there is a high number of COVID-19 cases. This study utilized a qualitative Husserlian phenomenological approach to describe and explore the lived experiences of the OFW nurses’ caring for COVID-19 critically ill patients. The research key interview informants were eight ICU nurses who cared for COVID-19 patients in Dubai hospitals. Data saturation was reached. Data collection was done in 2020, and Collaizi’s method of data analysis was utilized.Results: A total of 135 significant statements were extracted from the interview transcripts. There were 36 formulated meanings generated, and four themes emerged from this study. The first theme is Challenges During the Pandemic with the following subthemes: Away from Home, Caring for the COVID-19 Patients, and Fear of the Unknown. The second theme is Patient Care during COVID-19 with the following subthemes: COVID-19 ICU Patient Care and The Nursing Profession. Third, Adapting to Change with the subthemes: Living the New Normal and Protecting One’s Self from COVID-19. Lastly, Resilience Amidst the Pandemic with the following subthemes: Being with Others and Seeing Oneself.Conclusion: Despite the existing challenges like cultural differences and homesickness faced by these OFW nurses and the new challenges they are faced with the pandemic today, they were still able to continue living and do what is expected of them. From the hassle of wearing the PPEs, shortage of PPE, and being transferred from one unit in the hospital to another, the OFW nurses were able to adapt to these changes. The nurses already got used to the routine, but the fear of getting infected by the virus is still there.